2020
DOI: 10.1080/1478422x.2020.1770414
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of service life and corrosion mechanism of tubing in production well on polymer flooding

Abstract: The corrosion behaviour and the remaining safe service life of tubing in simulating production well of polymer flooding in Xinjiang oilfield which located in China was investigated using weight loss measurement and surface characterisation. The results showed that as the chloride ion concentration, temperature and H 2 S content increased, the corrosion rate of N80 steel gradually increased in the hydrolysis of anionic polyacrylamide (HPAM)/H 2 S/CO 2 environment. The tubing of production well met the requireme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…As observed, all polarisation curves showed that the corrosion process was controlled by anodic reaction. Compared to no obvious distinction of corrosion potential among different conditions, the wide potential domain occurred in the anodic process, and an active current peak appeared, which was related to the formation of Cr oxides [21,22]. The potential domain of 1Cr steel without silty sand was the lowest.…”
Section: Resultsmentioning
confidence: 99%
“…As observed, all polarisation curves showed that the corrosion process was controlled by anodic reaction. Compared to no obvious distinction of corrosion potential among different conditions, the wide potential domain occurred in the anodic process, and an active current peak appeared, which was related to the formation of Cr oxides [21,22]. The potential domain of 1Cr steel without silty sand was the lowest.…”
Section: Resultsmentioning
confidence: 99%
“…According to the weight-loss corrosion rate and pitting corrosion rate, the remaining corrosion life calculation model of tubing is established [33][34][35]. The core idea of the theory is that when the remaining wall thickness reaches its minimum allowable wall thickness, the service time of the tubing is its finite life.…”
Section: Finite Service Life Calculation Of Corrosion-resistant Alloy...mentioning
confidence: 99%
“…Moreover, the corrosion factors of tubing in polymer flooding production wells also include wellbore temperature, CO 2 content, and Cl − content. [11][12][13][14] As is well known, temperature plays an important role in the process of tubing corrosion. [15][16][17] Generally, scholars have proposed that the corrosion rate peak is usually between 80°C and 90°C in CO 2 corrosion where the temperature accelerates the reaction process and increases the corrosion rate of bare steel at the initial stage of corrosion.…”
Section: Introductionmentioning
confidence: 99%